Comparison of oral health self-assessment results in pregnant women in rural and urban areas: Study quantitative - Nugraha, Rega Mahesa; Suwargiani, Anne Agustina; Aripin, Dudi (Padjadjaran Journal of Dental Researchers and Students, 2023)
ABSTRACTIntroduction: Pregnant women are a group of people who are vulnerable to oral health problems due to physical, biological, and hormonal changes. Geographical and administrative location also affects oral health based on the ease of access to health services, which are divided into rural and urban areas. This study aims to analyze the oral health self-assessment of pregnant women in rural and urban areas. Methods: This study employed a quantitative comparative analytical approach with a cross-sectional data collection design, focusing on pregnant women residing in both rural and urban areas. A self-assessment tool, namely the "oral health questionnaire for adults"  developed by WHO, was used and already translated into Indonesian. The data were analyzed using the chi-square test. Results: This study included 159 pregnant women from both rural and urban areas, with an average age of 27.19 years.  The results of the self-assessment showed a difference in the educational background of pregnant women in urban areas, which is higher compared to those  in rural areas. The majority of pregnant women assessed that the condition of their teeth and gums was in moderate criteria; the self-assessment of cleaning the oral cavity and visiting the dentist of pregnant women in urban areas was better than that of pregnant women in rural areas; but pregnant women in urban areas were more likely to consume sweet foods and drinks. statistical tests indicate that the comparison has a significant value with a value of p<0.05. Conclusions: There were differences in dental hygiene practices, dentist visit frequency, and educational attainment among urban and rural pregnant women. There was no significant difference in assessing the condition of teeth and gums, using dentures, or experiencing dental and gum issues among pregnant women.KEY WORDS: pregnant women, oral health, rural-urban, self assessmentPerbandingan self assessment kesehatan gigi dan mulut pada ibu hamil di daerah rural dan urban: Studi cross sectionalABSTRAK Pendahuluan: Ibu hamil merupakan satu kelompok masyarakat yang rentan terhadap masalah kesehatan gigi dan mulut, dikarenakan adanya perubahan fisik, biologis, dan hormon. Letak geografis dan administratif juga memengaruhi kesehatan gigi dan mulut berdasarkan kemudahan akan akses pelayanan kesehatan yang terbagi menjadi wilayah rural dan urban. Penelitian ini bertujuan menganalisis self assessment kesehatan gigi dan mulut pada ibu hamil di daerah rural dan urban. Metode: Penelitian ini menggunakan jenis penelitian kuantitatif, yaitu analitik komparatif, dengan desain pengumpulan data cross sectional, dilakukan pada ibu hamil di daerah rural dan urban. Pemeriksaan dilakukan dengan menggunakan self assessment yaitu “Oral Health Questionnaire for Adults” dari WHO yang diterjemahkan ke Bahasa Indonesia. Analisis data penelitian menggunakan uji chi-square. Hasil: Penelitian ini diikuti oleh 159 ibu hamil yang berasal dari daerah rural dan urban dengan usia rata-rata ibu hamil adalah 27.19 tahun. Hasil self assessment memperlihatkan perbedaan pendidikan ibu hamil di daerah urban lebih tinggi dari daerah rural. Mayoritas ibu hamil menilai bahwa kondisi gigi dan gusinya dalam kriteria sedang; self assessment membersihkan rongga mulut dan mengunjungi dokter gigi ibu hamil di daerah urban lebih baik daripada ibu hamil di daerah rural; tetapi ibu hamil di daerah urban lebih cenderung mengkonsumsi makanan dan minuman manis. Hasil uji statistik yang menunjukkan perbandingan memiliki nilai signifikan dengan nilai p<0.05. Simpulan: Terdapat perbedaan nilai self assessment praktik kebersihan gigi, frekuensi kunjungan ke dokter gigi, dan tingkat pendidikan di antara ibu hamil di daerah rural dan urban dan tidak ada perbedaan nilai self assessment kondisi gigi dan gusi, penggunaan gigi tiruan, dan pengalaman masalah gigi dan gusi diantara ibu hamil.KATA KUNCI: ibu hamil, kesehatan gigi dan mulut, rural-urban, Self assessment